Behavior Change Based on Local Wisdom - Ramadhani, Firdausi; Rahmawati, Rahmawati; Maesarah, Maesarah; Hatta, Herman; Susanti, Inne (Poltekkes Kemenkes Palu, 2024)
The KB Village Program is an icon of BKKBN that can directly contact and provide benefits to the Indonesian people at all levels of the region. Programs related to stunting prevention have been provided but are not running optimally. Local wisdom is all forms of knowledge, beliefs, understanding, and insights as well as customs or ethics that demand human behavior in life in ecological communities. Various local values or wisdom are expected to be able to reduce stunting cases. This research uses a qualitative method with a case study approach. The population in this study are some of the people who live in Tolango Village, Anggrek Subdistrict, village officials and officials who handle the stunting program. The purpose of this research is expected to be able to provide education to the community, government and families regarding the right information in handling stunting. It is necessary to provide education to the community through appropriate health promotion means to reduce stunting cases in collaboration with religious leaders in conducting socialization to the community based on local wisdom by involving religious, traditional, community and government leaders. The local wisdom of